PENDIDIKAN KARAKTER DALAM PERSPEKTIF ISLAM UNTUK SISWA SD : Solusi Bagi Problematika Pendidikan Sekolah Dasar Islam Terpadu Di Era Modern - diah novita fardani (Al-Mudarris: Journal Of Education, 2018)
Character education in elementary school is an attempt to build character Elementary Students.Character education can be called as akhlak (moral) education, which aims to establish akhlak karimah. The foundation of character education in Islam is the Quran and Hadith. The process of character education to elementary school students should be tailored to the stage of development and the formation of character at this age, in elementary operations can use the model Tadzkirah (Teladan=exemplary, Arahkan=aim, Dorongan=encouragement, Zakiyah=purify, Kontinuitas=continuity, Ingatkan=remind, Repitition, Organize, Heart).